Federalism and the constitution of Canada - Smith, David E., 1936-2023 (Toronto [Ont.] : University of Toronto Press, 2010)
In Federalism and the Constitution of Canada, award-winning author David E. Smith examines a series of royal commission and task force inquiries, a succession of federal-provincial conferences, and the competing and controversial terms of the Constitution Act of 1982 in order to evaluate both the popular and governmental understanding of federalism. In the process, Smith uncovers the reasons constitutional agreement has historically proved difficult to reach and argues that Canadian federalism 'in practice' has been more successful at accommodating foundational change than may be immediately apparent."--Pub. desc.
"The Canadian system of federalism divides the power to govern between the central federal parliament and the provincial and territorial legislative assemblies. In what can be seen as a double federation, power is also divided culturally, between English and French Canada. The divisions of power and responsibility, however, have not remained static since 1867. The federal language regime (1969), for example, reconfigured cultural federalism, generating constitutional tension as governments sought to make institutions more representative of the country's diversity.
1 Primary Matters: Federalism and the Constitution -- 2 The Measure of Freedom -- 3 'A Constitution in Some Respects Novel' -- 4 Parliamentary Federalism -- 5 The Practice of Federalism -- 6 Courts and Charter: Constitution and Federalism -- 7 The Habit of Federalism.
Includes bibliographical references (pages 193-213) and index.
JSTOR
Keywords: Canada; Canada; Canada; Canada; Constitution Act, 1867 (Canada); Constitution Act, 1982 (Canada); Federal government -- Canada; Constitutional history -- Canada; Constitutional law -- Canada; Canada -- Politics and government; Canada -- Politique et gouvernement; Fédéralisme -- Canada; Canada -- Histoire constitutionnelle; Droit constitutionnel -- Canada; Histoire constitutionnelle -- Canada; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Constitutions; Constitutional history; Constitutional law; Federal government; Politics and government; Canada